Draft AMAP Strategy: 2004+. AMAP Report 2004:x. (DRAFT) - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2004)
"The Arctic Monitoring and Assessment Programme (AMAP) is an intergovernmental programme under the Arctic Council. AMAP was established in 1991 to implement components of the Arctic Environmental Protection Strategy (AEPS). In June 1997, the AEPS and its groups were subsumed under the responsibilities of the Arctic Council. The current AMAP mandate is a result of decisions initially taken during AEPS, and since 1998, Arctic Council Ministerial meetings. Details are available in the Rovaniemi (1991), Nuuk (1993), Inuvik (1996), Alta (1997), Iqaluit (1998), Barrow (2000), and Inari (2002) Ministerial Declarations. The AMAP Strategy 2004+ is developed in accordance with this mandate." /./